Disseminated sporotrichosis in an immunocompetent patient: an unusual presentation - Chu, Ee Seow; Wan Ahmad Kammal, Wan Syazween Lyana; Jamil, Adawiyah; Wan Ahmad Kammal, Wan Syahira Ellani; Chuan, Hun Ding (Remedy Publications, 2022)
Systemic sporotrichosis with cutaneous and pulmonary involvement in an immunocompetent patient is rare. We herein report a case of a 50-year-old man who presented with fever and multiple painful nodules for 1-month duration. On examination, there were hyperpigmented fluctuant subcutaneous nodules with hemorrhagic crusts on the face, trunk and extremities. Skin biopsy revealed acute suppurative granulomatous inflammation and panniculitis with budding yeasts. Chest X-ray demonstrated multiple centrilobular lung nodules at right upper lung zone and CT scan of the thorax showed consolidation over the peribronchovascular of right upper lobe, irregularity of the apical branch of right upper lobe bronchus and right hilar lymphadenopathy. Fungal culture from the skin nodule and bronchoalveolar lavage yielded Sporothrix schenckii. All investigations for immunocompromised state were negative. He was commenced on oral itraconazole which resulted in improvement of his symptoms. This case report highlights the rarity of sporotrichosis affecting the skin and lung simultaneously in an individual with a competent immune response.